Dampak Trichinella sp. dalam Daging Babi Terhadap Kesehatan Masyarakat - Engki Zelpina; Evie Setyani; Vinsen Willy Wardhana (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2021)
Trichinellosis/Trichinosis is one of the most common zoonotic parasites in the world caused by infection with Trichinella nematodes. The infection occurs after the larvae have been eaten in the muscles of the infected animal. Due to its spread and spread, several outbreaks of trichinosis have occurred around the world, which has caused serious public health problems. The main risk factor for trichinosis is the consumption of raw or undercooked meat from pigs and hunted meat. In the first stage of infection, adults nematode in the intestine can cause transient gastroenteritis, but the most serious symptoms are associated with the larval formation and muscle migration. a study conducted in India to investigate at the clinical and biochemical profile of Trichinella infection stated that clinical symptoms first appeared at 2-3 weeks after consuming pork and the symptoms would gradually disappear at 4-5 weeks, but there were also some who experienced myalgia. Supervision and implementing proper biosecurity in livestock areas by monitoring and surveillance of the risk of Trichinella infection in pig products and their derivatives as well as preventing transmission to humans.